2016
DOI: 10.1016/j.pmrj.2015.12.007
|View full text |Cite
|
Sign up to set email alerts
|

An Analysis of Inpatient Rehabilitation Approval Among Private Insurance Carriers at a Cancer Center

Abstract: Background Acute inpatient rehabilitation is often utilized by cancer patients to assist with discharge home and/or preparation for further treatment. Private insurance patients often require approval before transfer to acute inpatient rehabilitation. Objective To analyze the approval rate of private insurance carriers for acute inpatient cancer rehabilitation. Design Retrospective Analysis Setting Tertiary Referral Based Cancer Center Patients Ninety-six consecutive unique patients with private insura… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…For example, publications in the Surgical Intervention cluster are prominent; however, this research is poorly linked to the Therapeutic Intervention cluster. This may be driven by barriers to research and care and the complexities of payment models that are often prohibitive to aligning therapeutic interventions with postacute rehabilitation services (25), which may deter such research. Newer models such as prehabilitation and Early Recovery After Surgery (ERAS), studied in the colorectal and lung cancer populations, could help to improve the linkages between surgical interventions and therapeutic interventions for preventive, restorative, and supportive care (26)(27)(28).…”
Section: Discussionmentioning
confidence: 99%
“…For example, publications in the Surgical Intervention cluster are prominent; however, this research is poorly linked to the Therapeutic Intervention cluster. This may be driven by barriers to research and care and the complexities of payment models that are often prohibitive to aligning therapeutic interventions with postacute rehabilitation services (25), which may deter such research. Newer models such as prehabilitation and Early Recovery After Surgery (ERAS), studied in the colorectal and lung cancer populations, could help to improve the linkages between surgical interventions and therapeutic interventions for preventive, restorative, and supportive care (26)(27)(28).…”
Section: Discussionmentioning
confidence: 99%
“…48 Additional factors that limit subacute rehabilitation services include payer limitations and provider awareness and attitudes regarding the benefits of rehabilitation. 49,50 Home care…”
Section: Cancer Rehabilitation Clinical Models Postacute Carementioning
confidence: 99%
“…Fourth, payer/insurance limitations are issues. Although the approval rate of IRF rehabilitation can vary significantly by insurer, it has been reported that 87% of private insurance authorization requests for acute inpatient cancer rehabilitation are approved [75].…”
Section: Medical Fragilitymentioning
confidence: 99%